-
The curve y=1 x 2 can be converted to the power of minus thirds of y=x.
Derivative: y'=
2 3) x to the minus five-thirds power.
So substituting x=1 into y' gives the tangent equation of y'=-(2 3) so the curve y=1 x 2 at the point (1,1).
The slope of is k=-(2 3).
From the point oblique formula: y-1=-(2 3)(x-1), that is, 2x+3y-5=0
-
First, find the derivative of the curve to get y'=3x squared, and then bring in the tangent abscissa to get k=3, so the tangent equation is y=3(x
Then it's a matter of simplifying to get y3x
-
Doing this kind of problem is equivalent to finding the equation of a straight line, and the point on the straight line is known, now you only need to know the slope of the straight line, isn't it? So take this curve as a derivative.
y'=3x^2
Put the thought x=-1 generation into it, and get y'=3
So the slope of this straight line is 3
And the dot (-1,1).
Get. y=3x+4
-
Let the tangent equation for the curve y=x -x+3 be y1=kx1+b, then.
k=y'=(x³-x+3)'=3x²-1
The slope k at this point (1,3) is.
The intercept b of the tangent equation of k=2 is .
b=3-2×1=1
So the tangent equation at the point (1,3) is.
y1=2x1+1
-
First; 2b, point a(-1, let the tangent of a be tangent to the curve of b(b, b tangent equation: yb 3x
The tangent slope of the crossing b k3b
y'3b²(xb)
a on the tangent; 3b²
There is a real root, about b
b³3b²(-1b)
b 3b 3b ,1) is not on the curve (x1,y
-
y=x^3+x+1
y'=3x²+1
The slope of the tangent at the point (1,3) k=3 1 +1=4 curve y=x 3+x+1 The tangent equation at the point (1,3) is: y-3=4(x-1).
That is, y=4x-1
-
Summary. Please describe your problem more specifically, you can use ** and other forms, and talk to the teacher in detail, so that the teacher can better help you.
Tangent equation for the curve y=2-3x x at the point (1,-1).
Please describe your problem more specifically, you can use ** and other forms, and talk to the teacher in detail, so that the teacher can better help you.
What's that curve of yours? <>
**Question (2).
-
y'=ln3*3^x
According to the tangent equation y-y0=f'(x0)(x-x0) gives y-3=ln3*3*(x-1).
So the tangent equation laughs and quarrels with a basis of y=3(ln3)(x-1)+3
-
Derivative of the curve equation: y'=6x^2
The tangent slope of the curve at points (1,3) is: k=y'|x=1=6
Therefore, the tangent equation is: y-3=6(x-1), i.e., y=6x-3
-
Solution: First search for the curve y=x 3.
Y derivative = 3x 2
It is found according to the general equation of the straight line y=kx+b.
y=kx+b, through (1,1) cut k=3, b=-2 with people, the curve is arranged in y=x3, and the tangent square celery is in the (1,1) point.
is y=3x-2
-
y=x (-2 3), derivative=
2 3x (-5 3), the tangent slope of the eggplant k=
2 3, so y-1=
2 3 (x-1), the tangent party knows the process is 2x+3y-5=0
-
Answer: y=3x-2 itself is a straight line through the point (1,1) there is no tangent line, and its tangent line is the straight imitation of the envy line itself.
y=(3^x)-2
Lead-seeking. y'(x)=(3^x)'-0
3^x)ln3
y'(1)=3ln3
So: at point (1,1).
Tangent equations. is y-1=3ln3(x-1).
-
∵y=x^3-1
y'=3x²
then y'(1)=3 is the slope of the tangent at the point (1,0) The tangent equation is: y-0=3(x-1), that is, 3x-y-3=0 and the slope of the normal is -1 3
The normal equation is: y-0=-1 3*(x-1), that is, x+3y-1=0 [middle school students' mathematics, physics and chemistry] team will answer for you! I wish you progress in your studies, and you can ask if you don't understand!
-
Tangent: The derivative is y'=3x 2, at x=1, the derivative is 3So the tangent slope is 3, and with the point slope formula, the tangent equation is y= 3(x-1).
Normal: The slope of the normal is -1 3The same point oblique, y=-1 3 (x-1).